PEMBERDAYAAN BUDIKUNGDAMPER SEBAGAI BENTUK STRATEGI KETAHANAN PANGAN DAN EKONOMI DALAM MASA PANDEMI DI DESA ARYOJEDING TULUNGAGUNG - Nailariza Umami; Novita Eka Muliawati (JPM PAMBUDI, 2020)
During the Covid-19 pandemic, which has been running for almost 1 year, of course it has had a profound impact on all aspects of community life, especially the economy, which automatically creates another problem, namely the ability to provide family food. In terms of food security, people still lack knowledge and information. This also affects the level of creativity in the face of the Covid-19 pandemic to innovate in an effort to stabilize economic activity, especially in terms of food security. The aim of this service is to increase food security during the Covid-19 pandemic through Budikungdamper (Cultivating Fish and Water Spinach in Buckets). The methods used in this community service activity are lectures, discussions, demonstrations and hands-on practice. The work plan is programmed within 1 month.